Comparative Efficacy of Diverse Instructional Practices towards Enhancing the Academic Achievements of Students having Varied Learning Styles with Special Reference to Auditory Learners - Nair N, Sreevrinda (JOURNAL OF INDIAN EDUCATION, 2023)
Differentiated instruction and learning styles are closely related concepts in education. Differentiated instruction refers to the practice of tailoring instruction and learning experiences to meet the diverse needs and abilities of students in a classroom. It recognises the different modes of learning such as visual, auditory and kinesthetic based on their sensory modalities. Effective differentiation takes into account students’ learning styles as one of the factors influencing their learning. Educators can design instructional strategies and activities that better align with how students process information and engage with the learning material. It may offer different options for students to demonstrate their understanding of a concept. A teacher can address different learning styles and provides multiple entry points for students to access and express their learning. This experimental study explains the efficacy of select three differentiated practices on auditory students.